2022
DOI: 10.1007/s10753-022-01637-w
|View full text |Cite
|
Sign up to set email alerts
|

Lactylation: a Passing Fad or the Future of Posttranslational Modification

Abstract: Lactate is a glycolytic product and a significant energy source. Moreover, it regulates gene transcription via lactylation of histones and non-histone proteins, i.e., a novel posttranslational modification. This review summarizes recent advances related to lactylation in lactate metabolism and diseases. Notably, lactylation plays a vital role in cancer, inflammation, and regeneration; however, the specific mechanism remains unclear. Histone lactylation regulates oncogenic processes by targeting gene transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…Miar and colleagues reported a minimal role for HIF-1α or HIF-2α in regulating the hypoxic suppression of ISGs in cancer cell lines, but decreased chromatin accessibility of genomic regions relevant for type I IFN pathways (Miar et al 2020). Recent studies reported that lactate, a glycolytic product that is increased during hypoxia, regulates gene transcription via lactylation of histones (Xin et al 2022, Zhang, Tang, et al 2019). In tumor-infiltrating myeloid cells H3K18 lactylation increased N6-adenosine-methyltransferase 70 kDa subunit ( Mettl3 ) expression that modified Jak1 mRNA, thereby strengthening the immunosuppressive functions (Xiong et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Miar and colleagues reported a minimal role for HIF-1α or HIF-2α in regulating the hypoxic suppression of ISGs in cancer cell lines, but decreased chromatin accessibility of genomic regions relevant for type I IFN pathways (Miar et al 2020). Recent studies reported that lactate, a glycolytic product that is increased during hypoxia, regulates gene transcription via lactylation of histones (Xin et al 2022, Zhang, Tang, et al 2019). In tumor-infiltrating myeloid cells H3K18 lactylation increased N6-adenosine-methyltransferase 70 kDa subunit ( Mettl3 ) expression that modified Jak1 mRNA, thereby strengthening the immunosuppressive functions (Xiong et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Miar and colleagues reported a minimal role for HIF-1α or HIF-2α in regulating the hypoxic suppression of ISGs in cancer cell lines, but decreased chromatin accessibility of genomic regions relevant for type I IFN pathways [13]. Recent studies reported that lactate, a glycolytic product that is increased during hypoxia, regulates gene transcription via lactylation of histones [53,54]. In tumor-infiltrating myeloid cells H3K18 lactylation increased N6-adenosine-methyltransferase 70 kDa subunit (Mettl3) expression that modified Jak1 mRNA, thereby strengthening the immunosuppressive functions [55].…”
Section: Discussionmentioning
confidence: 99%
“…We have linked PD-L1 regulation of type I IFN to lactate produced during Warburg metabolism. Lactate is no longer considered simply a waste product, and is now known to be involved in the regulation of key oncogenes and tumor suppressor genes ( 58 ) as well as inflammation ( 59 ), and a novel post-translational modification (lactylation) involving addition of lactate to lysine and phenylalanine residues has been shown ( 60, 61 ).…”
Section: Discussionmentioning
confidence: 99%